Examining the causes and patterns of intended cesarean sections: A cross-sectional study in Dhaka, Bangladesh - Muniruzzaman, Md; Siddiky, Md Roknuzzaman; Ahmad, Faiyaz; Islam, Md Shihabul (Nurture, 2025)
Purpose: Cesarean section is an alternative method of childbirth that is generally applied when vaginal delivery encounters any unusual complications. However, nowadays, these types of deliveries, whether intended or unintended, have been increasing at an alarming rate in various countries worldwide. As such, the main purpose of this study was to investigate the causes and patterns of cesarean deliveries in Bangladesh. Design/Methodology/Approach: A mixed approach was employed to collect diversified data from the respondents. Primary data were collected for the survey through face-to-face interviews with 100 sampled respondents using snowball sampling. Additionally, four key informants were interviewed in-depth for a better understanding of the phenomenon under study. Findings: The study shows that despite there being no unavoidable complications in vaginal delivery, customers chose CS delivery for specific reasons such as convenience, fear of labor pain, concerns about their children’s birthdays, suggestions from healthcare providers, and motivations from other familiar individuals. The study also indicates a significant difference between public and private hospitals regarding customer satisfaction with various healthcare services, including childbirth. Private hospitals are more likely to provide quality healthcare services, while public hospitals tend to offer healthcare services at lower prices. Conclusion: The study suggests that the relevant government authorities should undertake proper steps to reduce the increasing number of CS deliveries in Bangladesh. Researchers, policymakers, and non-governmental organizations should also come forward to raise awareness among the public by initiating various programs, campaigns, seminars, and conferences.